The great separation: Top earner segregation at work in high-income countries - Olivier Godechot; Paula Apascaritei; István Boza; Lasse Folke Henriksen; Are Skeie Hermansen; Feng Hou; Naomi Kodama; Alena Křížková; Jiwook Jung; Marta M. Elvira; Silvia Maja Melzer; Eunmi Mun; et al. (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2020)
Analyzing linked employer-employee panel administrative databases, we study the evolving isolation of higher earners from other employees in eleven countries: Canada, Czechia, Denmark, France, Germany, Hungary, Japan, Norway, Spain, South Korea, and Sweden. We find in almost all countries a growing workplace isolation of top earners and dramatically declining exposure of top earners to bottom earners. We compare these trends to segregation based on occupational class, education, age, gender, and nativity, finding that the rise in top earner isolation is much more dramatic and general across countries. We find that residential segregation is also growing, although more slowly than segregation at work, with top earners and bottom earners increasingly living in different distinct municipalities. While work and residential segregation are correlated, statistical modeling suggests that the primary causal effect is from work to residential segregation. These findings open up a future research program on the causes and consequences of top earner segregation.
Keywords: 330; work; earnings; segregation; inequality; elite